Nanomedicine-mediated recovery of antioxidant glutathione peroxidase activity after oxidative-stress cellular damage: Insights for neurological long COVID - Akanchise, Thelma; Angelov, Borislav; Angelova, Angelina (Journal of medical virology, 2024)
Nanomedicine for treating post-viral infectious disease syndrome is at an emerging stage. Despite promising results from preclinical studies on conventional antioxidants, their clinical translation as a therapy for treating post-COVID conditions remains challenging. The limitations are due to their low bioavailability, instability, limited transport to the target tissues, and short half-life, requiring frequent and high doses. Activating the immune system during coronavirus (SARS-CoV-2) infection can lead to increased production of reactive oxygen species (ROS), depleted antioxidant reserve, and finally, oxidative stress and neuroinflammation. To tackle this problem, we developed an antioxidant nanotherapy based on lipid (vesicular and cubosomal types) nanoparticles (LNPs) co-encapsulating ginkgolide B and quercetin. The antioxidant-loaded nanocarriers were prepared by a self-assembly method via hydration of a lyophilized mixed thin lipid film. We evaluated the LNPs in a new in vitro model for studying neuronal dysfunction caused by oxidative stress in coronavirus infection. We examined the key downstream signaling pathways that are triggered in response to potassium persulfate (KPS) causing oxidative stress-mediated neurotoxicity. Treatment of neuronally-derived cells (SH-SY5Y) with KPS (50 mM) for 30 min markedly increased mitochondrial dysfunction while depleting the levels of both glutathione peroxidase (GSH-Px) and tyrosine hydroxylase (TH). This led to the sequential activation of apoptotic and necrotic cell death processes, which corroborates with the crucial implication of the two proteins (GSH-Px and TH) in the long-COVID syndrome. Nanomedicine-mediated treatment with ginkgolide B-loaded cubosomes and vesicular LNPs showed minimal cytotoxicity and completely attenuated the KPS-induced cell death process, decreasing apoptosis from 32.6% (KPS) to 19.0% (MO-GB), 12.8% (MO-GB-Quer), 14.8% (DMPC-PEG-GB), and 23.6% (DMPC-PEG-GB-Quer) via free radical scavenging and replenished GSH-Px levels. These findings indicated that GB-LNPs-based nanomedicines may protect against KPS-induced apoptosis by regulating intracellular redox homeostasis.
Keywords: oxidative stress; Oxidative Stress; quercetin; antioxidancia; nanomedicine; postakutní syndrom COVID-19; neurony; reaktivní formy kyslíku; Lactones; Glutathione Peroxidase; Neurons; lidé; Quercetin; laktony; ginkgolidy; long COVID syndrome; nanočástice; Nanoparticles; COVID-19; glutathione peroxidase; Nanomedicine; Post-Acute COVID-19 Syndrome; COVID-19 Drug Treatment; Humans; oxidační stres; SARS-CoV-2; farmakoterapie COVID-19; Ginkgolides; Reactive Oxygen Species; nanomedicína; Antioxidants; ginkgolide B; glutathionperoxidasa